The Impact Of Market Power And Cost Efficiency On The Banks’ Financial Performance (An Empirical Study On Banks Listed On Damascus Securities Exchange (Latakia University Journal - Economic and Legal Sciences Series, 2021)
This research aims to study the effect of market power and cost efficiency on the financial performance of banks listed on the Damascus Stock Exchange during the period from 2012 to 2018, using a sample consisting of 11 traditional private banks.The results showed an adverse and statistically significant effect of market power as measured by the Hirshman Herfendall HHI index on financial performance, and a direct and statistically significant effect of cost efficiency on financial performance, which indicates the ability of banks to control input costs and strive to keep costs at a minimum in order to achieve higher returns.